High-Gain SIR Dual-Band Antenna Based on CSRR-Enhanced SIW for 2.4/5.2/5.8 GHz WLAN. (29th July 2020) - Feng, Caixia; Kang, Yongqiang; Dong, Lijuan; Wang, Lihong
Abstract : This paper presents a dual-band step impedance resonator (SIR) antenna based on metamaterial-inspired periodic structure of coupled complementary split-ring resonators substrate-integrated waveguide (CSRR-SIW). The antenna supports wireless local area networks (WLAN) bands at 2.4/5.2/5.8 GHz. The CSRRs and two branches of the SIR element are etched on the top and bottom metal surfaces of the substrate. The SIR element produces a fundamental frequency f 1 at 2.4 GHz and a second harmonic frequency f s2 at 5.7 GHz. Meanwhile, the CSRRs produces a resonant frequency at high-frequency band around 5.2 GHz, which can be combined with the second harmonic frequency f s2 at 5.7 GHz. The high-frequency bandwidth can then be broadened. The simulated and measured results show that the dual operation bands with bandwidths of 16% from 2.25 GHz to 2.64 GHz and 18.2% from 5 GHz to 6 GHz for | S 11| < −10 dB are achieved. Meanwhile, the proposed antenna has peak gains ranging from 6.5 dBi to 7 dBi and from 7 dBi to 7.7 dBi in the lower and upper bands, respectively. Compared with many previously reported dual-band antenna designs, the proposed antenna achieves comparable bandwidth performance and larger gain per unit area with a relatively smaller size. Moreover, the simple structure renders the proposed antenna has the advantage of easy-processable and cost-effective implementation.